Association between blood selenium levels and gestational diabetes mellitus: A systematic review and meta-analysis - Yan, Shuai; Su, Han; Xia, Yang; Yan, Zixuan; Gao, Yitao; Shi, Mengyuan; Liu, Huiyuan; Wen, Yu; Zhao, Yuhong; Chang, Qing (Frontiers in Nutrition, 2022)
Abstract Introduction: The association between blood (serum or plasma) selenium concentrations and gestational diabetes mellitus (GDM) has been evaluated in some studies. However, the reported findings are debatable, and only case-control and cross-sectional studies were included. Objective: This research aimed to assess the association between blood selenium levels and GDM by analyzing existing literature. To provide a reference for the prevention and treatment of GDM, we included prospective studies not included in previous studies to collate more high-quality evidence. Methods: The PubMed, EMBASE, and Web of Science databases were retrieved for literature up to April 2022, and relevant references were manually searched. Raw data from relevant studies were extracted, and a random effect model was adopted for meta-analysis. The total effects were reported as weighted mean differences. All data were analyzed using Stata 16.0 software. Results: Fifteen studies involving 950 pregnant women with GDM and 1678 healthy pregnant women were incorporated in the meta-analysis. Pregnancies with GDM had significant lower blood selenium levels than those with normal glucose tolerance (weighted mean difference = -9.77; 95% confidence interval: -14.26 to -5.29, P < 0.001). Subgroup analyses showed that the association between blood selenium levels and GDM was consistent in the residents of Asia and Africa, but not in European. This trend was significant in the second and third trimester subgroups, but not in the first trimester subgroup. Articles published in 2016–2021 also showed this trend, but those published before 2015 did not show significant results. This association was evident in both non-prospective and prospective studies. Conclusion: Lower blood selenium concentrations are associated with GDM as shown in our study. Therefore, supplementing an appropriate amount of selenium may be helpful for GDM prevention and treatment.